Spectators involved in the work of contemporary art (2019)
The interest of this article aims to describe the art after avant-gardeunderstanding from different parameters to which regulated the art object as an art ofrepresentation. Nowadays art has become the environment real and it has expanded intosocial and communicative actions involving the viewer in new forms of participation andaction. To analyze the changing role of the viewer it was taken as main reference theconcepts of game, party and symbol of Hans-Georg Gadamer as categories that help us tounderstand, to theorize and to approach to contemporary art. These three concepts showthat contemporary art demands an active and participatory audience able to immersethemselves in the aesthetic creation.